(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Determining the optimal path for the mobile robot for a given environment to reach the destination from the starting location is implemented in numerous ways. To obtain the optimal solution Genetic Algorithm (GA) is predominantly used in this research domain. While applying GA, initial solution space is created by randomly generated paths. In this study, the solution space ascertained is environment specific which is directly influencing the computational cost. Three strategies are characterized to construct the initial path depending on the three classified environments. The experiments are conducted with different maps and the outcomes are analyzed quantitatively as well as qualitatively to defend the proposed methodology.